Stapled Haemorrhoidectomy Compared with Milligan-Morgan Excision for the Treatment of Prolapsing Haemorrhoids: A Prospective Study - Zahid Sattar, Muhammad Saad Iqbal, Saliha Zahid, Fahad Rasheed, Adnan Baqir, Saeed Ahmad, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The Milligan-Morgan excision (MMH) and stapled haemorrhoidectomy (PPH) are widely used surgical techniques for prolapsing haemorrhoids. To compare the efficacy, safety, and postoperative outcomes of stapled haemorrhoidectomy versus Milligan-Morgan excision in Pakistani patients. Methodology: A prospective comparative cross-sectional study was conducted at the Department of Surgery, Sahiwal Teaching Hospital, Sahiwal, during the period 1/06/2023 to 30/11/2023 involving 60 patients undergoing either PPH (n=29) or MMH (n=31). Data on operative time, postoperative pain (VAS), hospital stay, and complications were collected and analyzed using descriptive statistics, independent t-tests, and Chi-square tests. Results: A total of 60 patients were enrolled, with 29 undergoing stapled hemorrhoidectomy (PPH) and 31 undergoing Milligan-Morgan hemorrhoidectomy (MMH). The mean operative time was significantly shorter in the PPH group (26.07 ± 5.01 minutes) compared to the MMH group (41.03 ± 7.04 minutes) (p < 0.001). Postoperative pain assessed via the Visual Analog Scale (VAS) was markedly lower in the PPH group, with a mean score of 3.17 ± 1.42 versus 7.55 ± 1.21 in the MMH group (p < 0.001). Correspondingly, hospital stay was significantly reduced following PPH (1.52 ± 0.57 days) compared to MMH (3.32 ± 0.70 days) (p < 0.001). Infection rates were also higher in the MMH group, with 18 patients affected versus none in the PPH group (p < 0.001). Anal stenosis was observed in 26 MMH patients compared to only 2 in the PPH group (p < 0.001). Conclusion: Stapled haemorrhoidectomy offers advantages over Milligan-Morgan excision in terms of operative duration, patient comfort, recovery speed, and lower complication rates, supporting its preference in clinical practice despite higher costs. Keywords: Stapled haemorrhoidectomy; Milligan-Morgan haemorrhoidectomy; prolapsing haemorrhoids; urinary retention; anal stenosis.